The Estimation of Diversity and Potential Utilization of Agroforestry Plants in Batara Village, Timor-Leste - Nelson Andre; Yanto Santosa; Agus Hikmat (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
In the context of conservation, the government of Timor-Leste and its partners work together to implement an agroforestry program to address the problem of forest loss which continues to be graded every year. This study aimed to estimate the level of plant species diversity and the potential benefits of agroforestry for the Batara Village community. Data collection was carried out on agroforestry land owned by farmers in Batara Village from December 2021 to January 2022 and data collection using the single plot method and census method, namely 10m x 10m seedlings, 40m x 40m sapling, 60m x 60m pole and 113,14m x 113,14m tree. Data for plant diversity can be analyzed using the margalef index, shannon wiener, and evenness, and the potential benefits of agroforestry using descriptive analysis. Based on the results of research on the diversity of plant species in agroforestry land in Batara village, 33 species of seedling and understorey, sapling level 19 species, pole level 17 species, and tree level 15 species and overall found 42 species of plants with 25 families and the results of descriptive analysis of respondents' interviews show that agroforestry can contribute from an economic point of view by 54.28%, from an ecological perspective to 32.95%, from a social perspective to 24.18% and from a cultural perspective to 6.1%.